A pilot study to assess serum potassium levels and haemolysis in red cell units - Sarijan, Nurimatussolehah; Md Noor, Sabariah; Mohd Fathullah, Tun Maizura; Osman, Malina; Seman, Zainina (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Percentage of haemolysis is widely used as a quality parameter to assess red blood cell viability in blood banking. In certain blood banks, serum potassium level is used due to the unavailability of the former test. The relationship between these two tests, however, is still unclear. The objective of this study is to determine the association between haemolysis measured using two different methods for quality control. Methods: A total of forty-four samples of packed red cell in citrate-phosphate-dextrose with optisol were randomly selected from donation drives. Nine millilitres of blood was collected weekly starting from day-2 of storage, followed by day-7, 14, 21, 28, 35 and 42 for assessment of red blood cell haemolysis by measuring serum potassium level and percentage of haemolysis. Results: These two parameters were correlated significantly with a positive moderate linear relationship on day 7, 21 and 28 with r = 0.393, 0.448 and 0.425, respectively and p-values less than 0.01. The linear regression analysis showed there was a significant regression equation which could be used to predict the serum potassium level from the percentage of haemolysis. Conclusion: There were significant increases in the percentage of haemolysis and serum potassium level in the packed red cell units with storage. The serum potassium level would be able to be predicted from the percentage of haemolysis using the regression equations on day 7, 21 and 28. The serum potassium measurement could be used as an alternative test to the percentage of haemolysis before issuing blood.